COBOY (ECO BOARD PLAY): INOVASI MEDIA PEMBELAJARAN ALTERNATIF BERBASIS PENDIDIKAN LINGKUNGAN DENGAN METODE KASMARAN - Maulidin, Ilham (Indonesian Journal of Educational Studies, 2018)
This educational program was conducted in Kampung Bojong, Pamagersari Village with the target are children aged 5-14 years. The methods are socialization, education, action, and advocacy activities equipped with COBOY learning media. In cognitive aspect, the results have showed an increase understanding and positive changes towards mindset of participants in managing environment based on the four aspects of assessment from the lowest 36.7% to 83.3% which can be seen from the results of pretest and posttest. Affectively, there has been an increase in skills and positive attitude of participants in maintaining the environment especially managing the waste. As effort to expand the benefits has also been carried out the socialization of Training of Trainer (ToT) in SDN 01 Jasinga and has cooperated with Bureau of HUMAS Ministry of Forestry and Environment (KLHK) RI in disseminating environmental education to schools.